Resource allocation techniques for interference mitigation in macro and femtocell heterogeneous network-based LTE system - Al-omari, Motea Saleh Mohammed (2017)
In wireless broadband access networks, most indoor environments encounter serious coverage problems due to non-line of sight transmission. Femtocells have been introduced as a cost-effective solution to improve cell coverage, enhance area spectralefficiency, and provide better Quality-of-Service (QoS) to mobile users. However, interference issue is considered the major technical challenge associated with femtocell deployment. This interference occurs mainly because the radio spectrum is limited; meanwhile, femtocells have to (fully/partly) share/reuse the same available licensed spectrum with existing macrocells in the network, resulting cross-tier interference. Furthermore, FBS not only provides coverage within the owner’s home, but also radiates outside, extending coverage to nearby houses, leading to co-tier interference among neighboring femtocells. This thesis investigates impact of density deployment for femtocell grids with either size (3x3) or (5x5) in the downlink performance in two-tier Heterogeneous Networks (HetNets) based Vienna LTE system level simulator. The thesis further presents two different approaches for mitigating cross-tier interference as well as minimizing cotier interference in two-tier HetNets. The first proposed hybrid approach consists of two combined schemes, termed as Resource Allocation based Fractional Frequency Reuse and Graph Connectivity algorithm (RAFFRGC). The second proposed interference mitigation technique is a full frequency reuse termed as Resource Allocation based Cuckoo Search Algorithm (RACSA). The RACSA technique targets to maximize system throughput for a specified interference threshold for the ultimate mitigation of cross-tier interference in two-tier HetNets .The simulation results showed that femtocell deployment improves overall average user throughput in the case of a low-density scenario when deploying femtocells one by one. However, for a high-density scenario, FBS grids deployment had no enhancement in terms of throughput and fairness. Additionally, densely deploying femtocell grids without interference management degraded throughput for macrocell users. The simulation results show that the proposed RAFFRGC is effective in terms of mitigating both cross-tier and co-tier interference at the same time. In addition, RAFFRGC improves average throughput for both macrocell and femtocell users, taking into account a worst-case scenario model for femtocell deployment as grids sized (3x3) or (5x5). Moreover, RAFFRGC offload computational complexity and cost of additional design from FBSs by utilizing the Femtocell Management System (FMS) to achieve interference coordination and resource allocation among FBSs. Furthermore, RAFFRGC maximizes resource blocks efficiency, guarantees QoS for all femtocell users, and can support large-scale femtocell grids deployment. The simulation results revealed that RACSA mitigates cross-tier interference and improves system performance. The performance evaluation showed that RACSA gives 38% and 21% higher in system throughput and a 14% and 35% increase in spectral efficiency, as well as a 55% and 33% reduction for the outage probability when assessment is contrasted with the results produced by genetic algorithm and auction algorithm respectively.